Profile of Laying Chicken Farm and Analysis of Factors Causing West Nusa Tenggara to Not Self-Sufficient in Producing Eggs for Consumption - Mohammad Hasil Tamzil; Budi Indarsih (Faculty of Animal Husbandry, University of Mataram, 2020)
The aim of this study is to collect profile of laying chicken farms in West Nusa Tenggara Province to understand factors causing the province to still not self-sufficient in producing egg for consumption purposes. Samples for the study was taken in Lombok Island as the central of laying chicken eggs production in West Nusa Tenggara Province. Samples were taken using Stratfied Random Samling method and were tracked using snow ball method. Data collected consists of primary data and secondary data. Primary data consists of profile of laying chicken farms and number of eggs brought to West Nusa Tenggara. On the other hand, secondary data consists of laying chicken population and number of egg production in the West Nusa Tenggara region and neighboring provinces (provinces in Java, Bali and East Nusa Tenggara). The data obtained were analyzed descriptively. The results showed that laying chicken farms in West Nusa Tenggara were dominated by small scale farms owning from 500 to 9,000 chickens. Most of the farmers tend to practice good farming system. The combination of low number of farmers and chickens population is the reason why West Nusa Tenggara still has to import 6,480 tons of consumption eggs per year.